2019
DOI: 10.1101/533299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contrasting patterns of ERK activation in the tail of the striatum in response to aversive and rewarding signals

Abstract: All custom-made materials will be shared upon reasonable request. Running title: ERK, dopamine and the caudal striatumKeywords: striatum, dopamine, ERK, D1R, D2R, psychostimulants ERK, dopamine and the caudal striatum 2 AbstractThe caudal part of the striatum, also named the tail of the striatum (TS), defines a fourth striatal domain. Determining whether rewarding, aversive and salient stimuli regulate the activity of striatal spiny projections neurons (SPNs) of the TS is therefore of paramount importance to u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 72 publications
4
13
0
Order By: Relevance
“…The uneven distribution was also observed in ICR mice (11 weeks; N = 3). The uneven distribution of D1R and D2R were also found in the cStr of Wistar (N = 3, Figure 7C) and Long-Evans rats (N = 3, Figure 7D), as reported previously (Gangarossa et al, 2019). As the same as mice, D2R-poor zone was always located at the most caudal part of the striatum, and D1Rpoor zone was rostral to and medial to D2R-poor zone, although the appearance (shape and size) was bit different from those in mice.…”
Section: Uneven Distribution Of Immunoreactivity Of D1r and D2r In The Caudal Striatum Across The Age And Speciessupporting
confidence: 88%
See 1 more Smart Citation
“…The uneven distribution was also observed in ICR mice (11 weeks; N = 3). The uneven distribution of D1R and D2R were also found in the cStr of Wistar (N = 3, Figure 7C) and Long-Evans rats (N = 3, Figure 7D), as reported previously (Gangarossa et al, 2019). As the same as mice, D2R-poor zone was always located at the most caudal part of the striatum, and D1Rpoor zone was rostral to and medial to D2R-poor zone, although the appearance (shape and size) was bit different from those in mice.…”
Section: Uneven Distribution Of Immunoreactivity Of D1r and D2r In The Caudal Striatum Across The Age And Speciessupporting
confidence: 88%
“…In transgenic mice, the uneven distribution of D1R and D2R expressing neurons in the cStr (Gangarossa et al, 2013(Gangarossa et al, , 2019Miyamoto et al, 2019). The present study with wild type C57BL/6J mice also showed the uneven distribution of D1R and D2R expressing neurons in cStr and the coordinates of the boundary of D1R-and D2R-poor zones appear to be coincidence (Figures 1A-C).…”
Section: Dual Pathway Neurons In D1r-and D2r-poor Zonessupporting
confidence: 69%
“…Here, we investigated whether bingeing modulated the DA-associated signaling machinery. Thus, we used the activation (phosphorylation) of the ribosomal protein S6 (rpS6) and the extracellular signal-regulated kinases (ERK) as functional readouts of DA-dependent molecular activity (Gangarossa et al, 2013a, 2013b, 2019; Valjent et al, 2019). We first investigated such molecular activations in bingeing mice before and after reward-diet consumption ( Figure 3A ) in the DS and NAc ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…The experiment was carried out in a fear conditioning apparatus (Imetronic, Pessac, France) 25 . It consists of two soundproof boxes with different contextual configurations.…”
Section: Auditory Fear Conditioningmentioning
confidence: 99%
“…The experiment was carried out in a soundproof shuttle box (Imetronic, Pessac, France)25 . The apparatus is made of two equal compartments (20 x 20 cm) separated by an opened door.…”
mentioning
confidence: 99%